Infected Diabetes Foot Ulcer to Bony Structure Treating with Polyhexanide and Covering with Skin Substitute: A Case Report - Sirikun, Jatuporn; Muangman, Pattadon; Namviriyachote, Nantaporn; Tianwattanatada, Suttipong (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Background: Diabetic foot ulcers are a common and challenging complication in patients with diabetes mellitus, often complicated by infection and poor wound healing. Effective management requires adequate infection control, wound bed preparation, and optimized healing environment. Case Presentation: A 67-year-old female with newly diagnosed type 2 diabetes mellitus presented with a non-healing plantar foot ulcer persisting for three weeks following hot water immersion. The wound was complicated by systemic infection and exposed plantar fascia. Surgical debridement was performed to remove necrotic tissue and reduce bacterial load. Wound cleansing with Prontosan® solution was employed to prevent biofilm formation. Periwound hyperkeratosis was trimmed, and dressings including Askina® Dressil and Askina® Heel were applied for moisture management and pressure offloading. Vascular assessments (ABI, TBI, TCOM) confirmed adequate perfusion. A biological skin substitute was subsequently used to promote tissue regeneration and wound closure. Results: Infection was effectively controlled, and granulation tissue formation was observed over the previously exposed fascia. Minimal biofilm was managed with Prontosan® irrigation. The wound depth decreased rapidly after application of the skin substitute, with accelerated healing noted without need for complex reconstructive surgery. Conclusion: Comprehensive wound care—including debridement, infection control, and the use of Prontosan® for biofilm management—plays a key role in treating complicated diabetic foot ulcers. Prontosan® may accelerate healing by reducing microbial burden, while advanced techniques help improve outcomes and limit invasive procedures.